2014
DOI: 10.1186/s12866-014-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and tobacco consumption affects bacterial richness in oral cavity mucosa biofilms

Abstract: BackgroundToday there are more than 2 billion alcohol users and about 1.3 billion tobacco users worldwide. The chronic and heavy use of these two substances is at the heart of numerous diseases and may wreak havoc on the human oral microbiome. This study delves into the changes that alcohol and tobacco may cause on biofilms of the human oral microbiome. To do so, we used swabs to sample the oral biofilm of 22 subjects; including 9 control-individuals with no or very low consumption of alcohol and no consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 60 publications
8
66
0
1
Order By: Relevance
“…Уменьшение количества представителей рода Granulicatella и Gemella у больных с ХОБЛ, вероятно, отражает большую распространенность табакокурения у данной группы по сравнению с больными БА (индекс курения: среднее (БА) = 2,647, среднее (ХОБЛ) = 58,0412; p <0,05), поскольку для данных бактерий показано снижение пред-ставленности в микробиоме ротовой полости в популя-ции курильщиков [28].…”
unclassified
“…Уменьшение количества представителей рода Granulicatella и Gemella у больных с ХОБЛ, вероятно, отражает большую распространенность табакокурения у данной группы по сравнению с больными БА (индекс курения: среднее (БА) = 2,647, среднее (ХОБЛ) = 58,0412; p <0,05), поскольку для данных бактерий показано снижение пред-ставленности в микробиоме ротовой полости в популя-ции курильщиков [28].…”
unclassified
“…A recent study of our group showed that the consumption of alcohol and tobacco severely reduces the number of bacterial species found in the oral mucosa [43]. Since these drugs appear to have a role in GACs, their impact in the microbiota has the potential to be important for disease development.…”
Section: The Gastric Microbiotamentioning
confidence: 99%
“…Species of commensal Neisseria have been isolated from gingival and subgingival plaque (Li et al, 2004), and the presence of neisserial species is an indicator of a healthy oral microbiome (Aas et al, 2005). The abundance of the neisseriae in the human oral cavity is significantly reduced in frequent smokers, and in those who frequently smoke and abuse alcohol (Thomas et al, 2014). Although the most extensive attempts to characterise neisserial biofilm formation have been made using the pathogenic members of the family, commensal strains of the neisseriae might potentially have more to reveal about the establishment and maintenance of the carrier state, which as discussed above is crucial to the development of anti-neisserial immunity.…”
Section: What Role Do Commensal Neisseria Play In Thementioning
confidence: 99%